2006
DOI: 10.1175/mwr3145.1
|View full text |Cite
|
Sign up to set email alerts
|

Object-Based Verification of Precipitation Forecasts. Part I: Methodology and Application to Mesoscale Rain Areas

Abstract: A recently developed method of defining rain areas for the purpose of verifying precipitation produced by numerical weather prediction models is described. Precipitation objects are defined in both forecasts and observations based on a convolution (smoothing) and thresholding procedure. In an application of the new verification approach, the forecasts produced by the Weather Research and Forecasting (WRF) model are evaluated on a 22-km grid covering the continental United States during July-August 2001. Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
409
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 468 publications
(457 citation statements)
references
References 19 publications
8
409
0
2
Order By: Relevance
“…To identify MCSs in observations and our simulation we use a new variation of afeature-based verification method called the method for object-based diagnostic evaluation (MODE) (Davis et al 2006(Davis et al , 2009) that incorporates the time dimension [MODE time-domain or short MTD; Clark et al (2014)]. MTD is part of the Developmental Testbed Centers (DTC) Model Evaluation Tools (MET; the current version is available online at http://www.dtcenter.org/met/ users/downloads/).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify MCSs in observations and our simulation we use a new variation of afeature-based verification method called the method for object-based diagnostic evaluation (MODE) (Davis et al 2006(Davis et al , 2009) that incorporates the time dimension [MODE time-domain or short MTD; Clark et al (2014)]. MTD is part of the Developmental Testbed Centers (DTC) Model Evaluation Tools (MET; the current version is available online at http://www.dtcenter.org/met/ users/downloads/).…”
Section: Introductionmentioning
confidence: 99%
“…MODE has been used successfully to detect biases in short-term weather forecasts (e.g., Davis et al 2006Davis et al , 2009Clark et al 2012;Mittermaier and Bullock 2013). It was reported that coarse-resolution forecast models produce too many large rain areas and underestimate rainfall intensities (e.g., Davis et al 2006;Wernli et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are the techniques of Ebert and McBride (2000); Davis et al (2006); and Marzban and Sandgathe (2006). Objectoriented techniques are quite intuitive and effective when the features are well defined and can be associated with the forecasts and the observations.…”
Section: Introductionmentioning
confidence: 99%
“…This verification tool for the evaluation of precipitation fields is an "Object-based" approach, in which forecast and observed areas of precipitation are represented and compared as objects, and characterized by attributes such as location, size, and intensity of the systems (Davis et al, 2006a;Brown et al, 2007;Davis et al, 2009). Besides, MODE is publicly available at the Model Evaluation Tools website (MET -www.dtcenter.org/met/users).…”
Section: Introductionmentioning
confidence: 99%